Approaches and Methods of Periodization in Literary History - Dr. N. Gh. Sarli (Literary Arts)
One of the most fundamental acts of historiography is to classify historical information in diachronic axis. The method of this classification or periodization shows the theoretical approach of the historian and determines the structure and the form of his history. Because of multiple criteria of analysis and various literary genres, periodization in literary history is more complicated than that of general history. We can distinguish two approaches in periodization of literary history, although these can be used together: extrinsic or social-cultural approach (based on criteria extrinsic to literature) and intrinsic or formalist approach (based on criteria intrinsic to literature). Then periodization in literary history can be formulated in different methods and may be based upon various criteria: chronological such as century, decade and year; organic patterns of evolution; great poets and writers; literary emblems and evaluations of every period; events, concepts and periods of general or political history; analogy of literary history and history of ideas or history of arts; approaches and styles of language; dominant literary norms. These methods actually are used together and everyone has adequacy in special kind of literary history. In periodization of Persian contemporary literature, some methods and models current in periodization of poetry have been applied identically to periodization of prose. Periodization based upon century, decade and year is the simplest and most mechanical method but sometimes certain centuries in some countries have symbolic and stylistic meaning, and decades were used often for subdivisions of literary history, especially nowadays with fast rhythm of literary change.Periodization according to organic patterns of evolution equates the changes of literary history with the life phases of an organism, and offers an account of birth, mature and death (and sometimes re-birth) of literary genres, but this method have been under question because the rhythm of literary change always does not follow smooth and coherent patterns. Now periodization based on great writers and poets is not current but still is the favorite method of periodization in high school textbooks of Iran. Periodization based upon literary slogans and movements often is used for subdivisions of literary history. In periodization of Persian literature, this method has been used rarely. Most of stories of Persian literature derive divisions of their subject-matter from general or political history. In these cases, the periods have symbolic meaning, and describing their traits, the literary historian considers mere literary criteria. Periodization in terms of some ideas derived from history of art and thought has its supporters and further opponents. Yet some concepts like Renaissance, Baroque and Mannerism have come from history of art to literary history.Seeking literary autonomous history, some literary historians accept dominant norms a base of periodization. Yet there is some disagreement in nature of dominant norms and on the other hand, the unity ascribed to literary periods is incomplete and relative.Different methods of periodization often are used simultaneously in periodizing a literary history. This combination of methods can be seen in names of literary periods. Names of literary periods come from different origins